Graphene anchored Ce doped spinel ferrites for practical and technological applications. Issue 6 (15th April 2020) - Qamar, Sabih; Akhtar, Majid Niaz; Aleem, Waqas; Rehman, Zia ur; Khan, Ammad Hassan; Ahmad, Ayyaz; Batoo, Khalid Mujasam; Aamir, Muhammad
Abstract: Graphene plays a remarkable role as a supporting material for the fabrication of a variety of nanocomposites. This work presents the fabrication of graphene-based Ce doped Ni–Co (Ni0.5 Co0.5 Ce0.2 Fe1.8 O4 /G) ferrite nanocomposites. Ni0.5 Co0.5 Fe2 O4 and Ni0.5 Co0.5 Ce0.2 Fe1.8 O4 were prepared using sol gel method. However, Ce doped Ni–Co spinel nanoferrite was chemically anchored on the surface of graphene. Different characterizations techniques were adopted to investigate the variations in the properties of ferrite composite due to the incorporation of graphene. Thermal analysis revealed 18% heat weight loss of Ce doped Ni–Co ferrite sample during treatment up to 1000 °C respectively. X-ray diffraction analysis depicted the presence of spinel phase structure of all synthesized nanocomposites. Fourier transform infrared analysis revealed two absorption bands of tetrahedral and octahedral sites of the spinel phase and presence of graphene contents in the Ni0.8 Ce0.2 CoFeO4 /G composite. FESEM images revealed an increased agglomeration due to the presence of graphene in the Ce doped Ni–Co ferrite composites. Graphene based Ce doped Ni–Co ferrite nanocomposite showed highest conductivity (4.52 mS/cm) than other ferrite composites. Magnetic characteristics showed an improvement in the Ni–Co ferrite sample by the substitutions of Ce 3+ ions and graphene contents. The improvement in the properties of these nanocomposites makes them potential material for many applications such as fabrication of electrodes, energy storage and nanoelectronics devices.